The Influence of Digital Literacy and Organisational Climate on Teacher Performance through Job Satisfaction as a Mediating Variable at CHIS School Bali - Dwita Utami, Ni Made Putri; Putu, Kepramareni; I Nengah, Aristana (International Journal of Scientific Research and Management (IJSRM), 2025)
This study aims to explore how digital literacy and organisational climate influence teacher performance, with job satisfaction as a mediating variable, within the context of CHIS School Bali. Adopting a quantitative approach, the research analyses the relationships among key variables that play a pivotal role in enhancing the quality of education. The study focuses on four essential dimensions: digital literacy, organisational climate, job satisfaction, and teacher performance. The entire teaching staff, from Playgroup to Senior High School, constituted the population, with a sample of 60 respondents selected for the analysis. The findings reveal that teachers’ proficiency in digital technology and a positive, supportive work environment significantly impact their job satisfaction and performance levels. More specifically, all proposed hypotheses in the study were statistically supported: both digital literacy and organisational climate exert direct and indirect effects on teacher performance, with job satisfaction as a significant mediating factor. The study concludes that when teachers possess strong digital literacy skills and operate within a conducive organisational climate, their job satisfaction increases, leading to enhanced performance outcomes. Recommendations include fostering active use of social media among teachers and students for sharing instructional content and school-related information, and organising regular meetings between teachers and school management to discuss issues and collaboratively seek solutions, building trust and promoting teamwork.